Implementation of Interdisciplinary Rapid Rounds in Observation Units. Issue 4 (October 2017) - Ryan, Lindsey; Scott, Stephanie; Fields, Willa
Abstract : Lack of collaboration and communication can lead to medical errors, increased length of stay, and diminished patient satisfaction. The purpose of this project was to improve nurse efficiency, interdisciplinary communication and collaboration, and patient satisfaction with the discharge process through Rapid Rounds. The results demonstrated that interdisciplinary communication and collaboration improved coordination of care, as evidenced by improved Press Ganey percentile rankings for readiness for discharge and speed of the discharge process, increased pharmaceutical interventions, and fewer phone calls to physicians. Abstract : Supplemental Digital Content is Available in the Text.